Analyzing the Impact of Narcotics through Maqasid Sharia: Toward Integrative Prevention Approaches - Isya Hanifa Kurnianto; Rifqi Rifqi (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
Drug abuse is a serious threat to the sustainability of human life. From the perspective of Maqasid Sharia, narcotics destroy the five main goals of Islamic law is protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-aql), progeny (hifz al-nasl), and property (hifz al-mal). This research aims to examine the dangers of narcotics within the framework of Maqasid Sharia and explore prevention solutions based on Islamic values. The method used is literature study by collecting data from Islamic references, scientific journals, and drug policy documents. The findings indicate that narcotics damage social, moral, and spiritual structures. These findings imply the importance of religious-based approaches to drug prevention in Indonesia. The study concludes that integrating Maqasid Sharia values into educational, social, and legal policies is essential to reduce drug abuse.